Genome and transcriptome sequence databases for discovery, storage, and representation of alternative splicing events - Taneri, Bahar; Gaasterland, Terry M. (Wiley, 2014)
This chapter describes the process of RNA splicing and focus on RNA alternative splicing. It provides a general overview of the widespread cellular phenomenon alternative splicing. The chapter explains the databases for Alternative Splicing Queries (dbASQ), a computational pipeline used to generate alternative splicing databases for genome and transcriptome sequences of various organisms. dbASQ enables the use of genome sequence and transcriptome sequence data of any given organism for database development. The general introduction to splicing and alternative splicing includes their mechanism and regulation. The chapter explains the content and the utility of alternative splicing databases for five different eukaryotic organisms: Human, mouse, rat, frutifly, and soil worm. It presents genomic and transcriptomic sequence analyses and data mining from alternative splicing databases in general. The chapter also provides an example illustrating the utility of the splicing databases (SDBs) on initial and terminal exon variation. © 2014 John Wiley & Sons, Inc. Published 2014 by John Wiley & Sons, Inc.